Cooperation in Space Traffic Management : The USA vs. the EU - Martínek, Patrik (2021)
The thesis deals with the evolving space traffic management (STM) in the context of the increasing activity in the near-earth environment. It identifies threats stemming from the lack of an internationally recognized space traffic management regime. Lastly, it provides a comparative case study of the US and EU approaches to space traffic management in the context of a globally accepted STM regime.